Development of The Project Approach in Engineering Higher Education - V. V. Glushchenko (Indonesian Journal of Educational Research and Technology, 2023)
The subject of this article is the methodological aspects of the development of project-based higher education at a machine-building university, the object of the article – higher education in mechanical engineering, the purpose of the article is to increase the efficiency of the processes of development of project higher education at the University of mechanical Engineering, to achieve this goal, the following tasks are solved: research of the essence of project education in mechanical engineering, clarification of the concept of "paradigm of development of project higher education in mechanical engineering", description of the structure and content of the elements of the structure of the paradigm of development of the named project education at the University of mechanical engineering, structure discussion, the essence and content of the directions of development of such project education; research methods are historical, logical, structural analysis, qualitative analysis, predictive analysis, synthesis, search and heuristic forecasting, heuristic assessments; scientific novelty of the work is associated with the study of the essence of project education in mechanical engineering and the formation of methodological foundations for the development of the concept and policy of development of project higher education in mechanical engineering universities in the interests of improving the quality of higher education.